Corporate Social Responsibility in the Maritime Industry (WMU Studies in Maritime Affairs,, 2018)
This book addresses the environmental, legal, social, and economic aspects of corporate social responsibility in the maritime industry. It discusses the voluntary aspects of the CSR concept and how the lines between informal and formal rules are merging and becoming fuzzy. Further, it shows how regulation is enhancing responsibility and sustainability in the maritime industry. The book gathers the experiences of the WMU, IMO, UN and public and private actors in developing and developed countries in the maritime industry.